Educação inclusiva e desenvolvimento sóciocognitivo - SILVA, Maria Santana da Costa da (2023)
The inclusion of children with multiple disabilities in regular education classrooms brings with them situation many challenges. The interest in elaborating this work with the theme Education Inclusive and socio-cognitive development arose from the need to understand ho the teaching-learning process and what repertoires of knowledge are taught to them and which are learned from an inclusive perspective. Supported by this objective, and with the intention to support the reflections, we raised the following issue: is the school prepared to receive these students? Does the government support or not the school with financial resources for the permanence of these students? Are teachers qualified to receive these students? At school what is happening is inclusion or integration? Within this perspective, the process The methodological framework of this work is based on a bibliographical and field research with a qualitative approach, using as data collection technique, semi-structured interview and non-participant observation. Thus, the inclusion process presents many obstacles, especially in the public school in the rural area and the challenges imposed due to this reality are diverse such as teacher training, lack of resources and precariousness of teaching.